Pengaruh Penggunaan Metode Ceramah terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS - Adisel, Adisel; Saputri, Icha Eka; Ulfah, Ahmad; Sudomo, Anggi Herlen; Alamsah, Samsani; Ulandari, Ulandari (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to see the effect of using the lecture method on student learning outcomes in social studies subjects for class VIII SMP. This type of research uses the observation method, namely by going directly to the field for observations and data collection needed in research. Then the data obtained were collected and analyzed descriptively. With reference to relevant journals/research and Syafril's (2019) book on learning strategies. The results of the study illustrate that the learning outcomes of class VIII A students at SMP 10 Bengkulu City get good grades when using the lecture method in the teaching and learning process. This is evidenced by the mid-semester test scores of students in social studies subjects who get scores above the KKM, namely 70. In conclusion, the selection of the right learning model can indeed increase student activity and creativity, so that student achievement can increase. This success can be seen from students' understanding, mastery of the material and learning outcomes. Keywords: Learning Outcomes, Lecture Method, Social Studies Lessons